The talent equation big data lessons for navigating the skills gap and building a competitive workforce - Ferguson, Matt (McGraw-Hill Education, 2014)
Authored by the CEO of CareerBuilder; this smart and timely guide offers hiring professionals and business leaders a roadmap to attract and retain top talent so you can drive your business forward. --
Includes bibliographical references and index. - Print version record
Keywords: Manpower planning; Skilled labor; Human capital -- Management; Employees -- Recruiting; Employees -- Training of; Vocational education; Inservice Training; Vocational Education; Main-d'uvre; Planification; Personnel; Recrutement; Personnel; Formation; Enseignement professionnel; Employees; Recruiting; Employees; Training of; Human capital; Management; Commerce; Business & Economics; Marketing & Sales